Finance and Development, June 1969. (Finance and Development; Finance and Development ;, 1969)
This paper presents a description of the Project Analysis Course offered by the World Bank's Economic Development Institute (EDI). The main objective of EDI is to give individuals a general understanding of all the main elements involved in preparing, evaluating, and executing development projects. At the end of the course, EDI expects graduates to be able to help design project studies or to participate in the overall evaluations on which final decisions are heavily based.